(Nt\MD\G N\R BAJMV UTGA ILTG\H NXs (NmAGISTRYN AVIL s - (NnARANC\C\G v(B.s; (NmONGOL uLSYN iH sURGUULXs ((Nubs, 2005)
(NdIPs
(NdIP(B-1920s
Keywords: (NH\L [INVL\Hs; (NMONGOL H\L s; (NT\MD\G N\Rs; (NMAGISTRYN DIPLOMYN AVILs